Effect of pH and pressure on syngas fermentation by anaerobic mixed cultures - Pereira, Filipa Maria Rodrigues (2013)
Syngas fermentation by mesophilic anaerobic mixed cultures was studied, regarding the effect of initial medium pH (5.8, 6.9 and 7.6) and total initial syngas pressure (1.0, 1.75 and 2.5 atm) in methane production and other alternative products (acids and alcohols). Complete consumption of CO and H2 was achieved in less than 72 h at 1.0 atm syngas, and within 240 h for higher syngas pressures. The highest specific CH4 production (normalized to the initial syngas concentration, CO+H2) was 0.89 mol CH4/mol syngas, and was obtained for pH 5.8 and 1.0 atm syngas. Volatile fatty acids (VFA) were produced in methanogenic-inhibited assays, with 0.92 mol VFA/mol syngas as the best conversion yield (at pH 6.9 and 1.0 atm). Only residual concentrations of alcohols (< 0.005 mol alcohols/mol syngas) were produced by methanogenic-inhibited sludge. Syngas pressure had a major effect on conversion yields, which might be related to the susceptibility of microbial communities to the higher CO partial pressures.